TIPE WISATAWAN BERDASARKAN KORELASI MOTIVASI DAN KEGIATAN DI TEMPAT WISATA (STUDI KASUS: INDONESIA) - Bakri Prakarso Andi Wiyono; Hanson E. Kusuma; Fran Sinatra; Angela Christysonia Tampubolon (Diponegoro University, 2019)
Tourism has become a major contributing sector in the economies of many countries in the world, especially Indonesia. The attractiveness of Indonesia comes from a variety of potential such as nature, local wisdom, or artificial. Those attractions make tourist can be defined as many types based on their motives and activities. This research used mixed method (qualitative-quantitative) with sequential procedure strategy. The purpose of this study is to determine the type of tourists based on the correlation between the motivation of travel with tourism activities. Data collection was done through an online questionnaire and distributed to several groups (nonprobability-convenience sampling). The collected data were then analyzed qualitatively using content analysis and quantitatively using principal component analysis, factor analysis, and multivariate correlation analysis. The results of the analysis revealed that there are six tourism motivations namely contemplation, social-exploration, restorative, culinary, opportunity, and novelty. In addition, there are four tourism activities namely physical activity, cognitive, affective, and adventure. The results of the correlation of motivation and tourism activities then form a pattern that shows three types of tourists such as explorer, pleasure seeker, and adventurer.